The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1115/1.2911462
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wing-Type Vortex Generators for Heat Transfer Enhancement in Channel Flows

Abstract: Longitudinal vortices can be generated in a channel flow by punching or mounting small triangular or rectangular pieces on the channel wall. Depending on their forms, these vortex generators (VG) are called delta wing, rectangular wing, pair of delta winglets, and pair of rectangular winglets. The heat transfer enhancement and the flow losses incurred by these four basic forms of VGs have been measured and compared in the Reynolds number range of 2000 to 9000 and for angles of attack between 30 and 90 deg. Loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
75
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(90 citation statements)
references
References 0 publications
1
75
0
Order By: Relevance
“…Their studies also showed that the vortices in the wake of the second row were more unsteadiness than the first-row vortices [6]. A pair of delta winglets performed slightly better than a pair of rectangular winglets at higher angles of attack and Reynolds numbers [8]. The results from studies by Biswas et al [9,10] indicated that the flow loss due to the winglet-pair was less than that due to the wing, and the zone of poor heat transfer as it was observed with the wing could be avoided by using winglet-pair.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Their studies also showed that the vortices in the wake of the second row were more unsteadiness than the first-row vortices [6]. A pair of delta winglets performed slightly better than a pair of rectangular winglets at higher angles of attack and Reynolds numbers [8]. The results from studies by Biswas et al [9,10] indicated that the flow loss due to the winglet-pair was less than that due to the wing, and the zone of poor heat transfer as it was observed with the wing could be avoided by using winglet-pair.…”
Section: Introductionmentioning
confidence: 88%
“…They found that the longitudinal vortex effects on the Stanton number were attributed largely to the distortion in the mean velocity field. Fiebig and his group [5][6][7][8] conducted systematic experimental investigations on heat transfer enhancement and induced drag using delta wings, rectangular wings, delta winglets and rectangular winglets in channel uniform flows. They found that the heat transfer was increased up to 60-degree angle of attack.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the reports of Tiggelbeck et al, 2 the best performance is given by the delta winglets, closely followed by the rectangular winglets (RWs). Russell 3 carried out experimental study of a pair of embedded VGs on the channel and compared their heat transfer and pressure drop characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The latter study investigates enhancement in heat transfer from a fin tube heat exchanger with winglets by disrupting the growth of thermal boundary layer and reducing the minimum surface heat transfer in the wake region directly down stream of circular tubes. In channel flow without cylinder, many works have been published using vortex generator to enhance heat transfer [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%